2020
DOI: 10.1016/s2352-3018(19)30436-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 90-90-90 on HIV-1 incidence and mortality in eSwatini: a mathematical modelling study

Abstract: Background The rapid scale-up of antiretroviral therapy (ART) towards the UNAIDS 90-90-90 goals over the last decade has sparked considerable debate as to whether universal test and treat can end the HIV-1 epidemic in sub-Saharan Africa. We aimed to develop a network transmission model, calibrated to capture age-specific and sex-specific gaps in the scale-up of ART, to estimate the historical and future effect of attaining and surpassing the UNAIDS 90-90-90 treatment targets on HIV-1 incidence and mortality, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 30 publications
1
32
1
Order By: Relevance
“…For instance, it is estimated that in the United States between 2014 and 2018 syphilis, chlamydia, and gonorrhea have increased in incidence by 71%, 19%, and 63%, respectively [1]. In contrast, HIV incidence has been decreasing worldwide [2], in part due to the UNAIDS 90-90-90 strategy [3].…”
mentioning
confidence: 99%
“…For instance, it is estimated that in the United States between 2014 and 2018 syphilis, chlamydia, and gonorrhea have increased in incidence by 71%, 19%, and 63%, respectively [1]. In contrast, HIV incidence has been decreasing worldwide [2], in part due to the UNAIDS 90-90-90 strategy [3].…”
mentioning
confidence: 99%
“…UNAIDS and the BaiHuaLin alliance of people living with HIV, with support of the Chinese National Center for AIDS/STD Control and Prevention, did a survey among people living with HIV in China in February, 2020. 5,6 Among this population, 32•6% were at risk of ART discontinuation and about 48•6% did not know where to get antiviral drugs in the near future. 5,6 People living with HIV who are faced with ART discontinuation not only could undergo physical health deterioration but also might suffer great psychological pressure.…”
mentioning
confidence: 99%
“…4 However, until UTT community-based trial results began to be reported 4 years ago, it remained unclear to what extent this remarkable increase in coverage translated into HIV prevention. In The Lancet HIV, Adam Akullian and colleagues 5 report that ART scale-up in eSwatini, which has the world's highest HIV prevalence, has largely been a success story, dramatically reducing adult HIV incidence and mortality. Using a mathematical model calibrated with demographic, HIV prevalence, and ART coverage data, they estimate that adult mortality decreased by more than 50% and HIV incidence by more than 40%, between 2010 and 2016.…”
mentioning
confidence: 99%
See 2 more Smart Citations